Effects of Dietary Protein Levels on Haemato-biochemical Response and DNA: RNA ratio of Pabda, Ompok bimaculatus (Bloch, 1794) - Jena, A. K.; Biswas, Pradyut; Arambam, Kalpana; Parhi, Janmejay; Pandey, P. K. (Fishery Technology, 2019)
Five iso-energetic semi-purified diets with varyinglevels of crude protein viz., P25 (25.10%), P30(29.93%), P35 (35.28%), P40 (39.73%) and P45(44.49%) were fed to Pabda, Ompok bimaculatusfingerlings (average weight 3.29Â±0.01 g) in triplicategroups (11 healthy fish per replicate) for a periodof 60 days to study the haemato-biochemicalparameters and nucleotide concentration of the fish.Fish were stocked in indoor plastic tanks, providedwith 500 l of aerated freshwater in each tank. Eachgroup was fed to satiation twice a day for 60 days.Significant differences were observed in haematobiochemicalparameter, RNA concentration andRNA:DNA ratios with different dietary proteinlevels. These parameters showed an increasing trendwith an increase in the dietary protein levels up toP35 diets (p